A positive but complex association between meiotic double-strand break hotspots and open chromatin in Saccharomyces cerevisiae - Berchowitz, Luke E.; Hanlon, Sean E.; Lieb, Jason D.; Copenhaver, Gregory P.

(untitled) (Genome Research, 2009)
During meiosis, chromatin undergoes extensive changes to facilitate recombination, homolog pairing, and chromosome segregation. To investigate the relationship between chromatin organization and meiotic processes, we used formaldehyde-assisted isolation of regulatory elements (FAIRE) to map open chromatin during the transition from mitosis to meiosis in the budding yeast Saccharomyces cerevisiae. We found that meiosis-induced opening of chromatin is associated with meiotic DSB hotpots. The positive association between open chromatin and DSB hotspots is most prominent 3 h into meiosis, when the early meiotic genes DMC1 and HOP1 exhibit maximum transcription and the early recombination genes SPO11 and RAD51 are strongly up-regulated. While the degree of chromatin openness is positively associated with the occurrence of recombination hotspots, many hotspots occur outside of open chromatin. Of particular interest, many DSB hotspots that fell outside of meiotic open chromatin nonetheless occurred in chromatin that had recently been open during mitotic growth. Finally, we find evidence for meiosis-specific opening of chromatin at the regions adjacent to boundaries of subtelomeric sequences, which exhibit specific crossover control patterns hypothesized to be regulated by chromatin.